Principles of studying Ukrainian as a foreign language: problems of theory (Pedagogy of Higher and Secondary Education, 2015)
Dyrda I. A. Principles of studying Ukrainian as a foreign language: problems of theory.The paper accentuates the essence of the term “principles of education”, the views of Ukrainian and foreign scientists concerning different principles of education are analyzed. Thepaper marks out general didactical and linguistic didactical principles of studying Ukrainian as a foreign language.
Keywords: principles of education; Ukrainian as a foreign language; principles of studying Ukrainian as a foreign language; general didactical and linguistic didactical principles